Professional Training in English: Laboratory Manual in General and Inorganic Chemistry: study aid - Machekhina K. I. Ksenia Igorevna (Tomsk, TPU Publishing House, 2024)
This Laboratory Manual is specifically designed for international and Russian bachelor students who study General and Inorganic Chemistry in English as part of their curriculum (14.03.02 Nuclear Science and Technology, 18.03.01 Chemical Technology, 19.03.01 Biotechnology). Given the theoretical and practical focus, the materials can be used to tailor learners’ needs not only in laboratory sessions, but also in lectures and tutorials.